2021
DOI: 10.21203/rs.3.rs-443322/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treatment patterns and Outcomes of Elderly Patients with Potentially Curable Esophageal Cancer 

Abstract: Background: The proportion of elderly patients with esophageal cancer (EC) is increasing due to prolonged life expectancy and aging process. However, the optimal treatment strategy for elderly patients (aged ≥70 years) with EC remains controversial.Methods: Eligible patients with cT1b-4aNxM0 EC were identified in the Surveillance, Epidemiology, and End Results database from 2010 to 2016. Treatment patterns were divided into five groups: surgical resection (S), chemoradiotherapy (CRT), radiotherapy (RT), chemot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Results showed that age was the independent risk factor for OS. 35 Regarding RFS, age and the depth of tumor invasion were independent factors. In terms of DSS, only age was the influential factor.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that age was the independent risk factor for OS. 35 Regarding RFS, age and the depth of tumor invasion were independent factors. In terms of DSS, only age was the influential factor.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, despite 60% of the patients being over 65 years of age at the time of diagnosis, current treatment guidelines for esophageal cancer do not discriminate between fit and frail older adults (3). Both chronological age and frailty are associated with higher postoperative complication rates and mortality, and chemotherapy toxicity (9)(10)(11). In addition, we recently reported a high prevalence of geriatric deficits in older patients with curable esophageal cancer that was subsequently associated with high chemoradiotherapy discontinuation rates (12).…”
Section: Introductionmentioning
confidence: 99%